The Pedagogical Benefits of Participatory GIS for Geographic Education. Issue 4 (4th July 2017) - Sinha, Gaurav; Smucker, Thomas A.; Lovell, Eric J.; Velempini, Kgosietsile; Miller, Samuel A.; Weiner, Daniel; Wangui, Elizabeth Edna
ABSTRACT: In this article, participatory GIS (PGIS) is explored and established as a powerful platform for geographic education. PGIS pedagogy can help educators meet diverse learning objectives pertaining to: (1) local knowledge and place-based thinking; (2) community engagement; (3) field mapping with geospatial technologies; (4) mixed-methods research; and (5) fostering of critical reflexivity in students. The discussion is supported with insights from multiple student-facilitated PGIS projects organized in rural Tanzania. There also is a thorough discussion of the challenges and caveats associated with involving students in PGIS projects, and a call for new research for assessing and advancing PGIS pedagogy.